Nutritional Status Measurement Using CIAF and Its Determinants in Flood-Affected Toodlers in Sidomulyo Village, Bumiaji, Batu - Handini, Laksmi Suci; Durry, Fara Disa; Febriawan, Zulfan; Ruswan, Farida Nayla Kholilah; Dzikro, Mir Atudz; Shafira, Aisyah Nur; Pratama, Salsabilla Haya (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2025)
Background: Flooding often leads to malnutrition among children under five, driven by limited access to nutritious food and unsanitary conditions. Sidomulyo Village in Batu City, prone to flooding due to the Paron River overflow, has faced challenges affecting the nutritional status of children. Objective: this research aims to analyze the nutritional status and its determinants using the CIAF Index for children under 5 years old affected by flooding in Sidomulyo Village, Bumiaji District, Batu City, Indonesia. Methods: This analytical observational study involved 20 pairs of mothers and children under five residing in Sidomulyo Village. Anthropometric measurements were conducted by calculating their z-scores and classifying their nutritional status using the Composite Index of Anthropometric Failure (CIAF). Interviews were conducted to gather data on maternal, child, and sanitation characteristics. Data analysis was performed using SPSS version 23.0, including descriptive analysis and Chi-square tests to examine relationships (P < 0.05). Results: The findings revealed that 68.75% of toddlers in Sidomulyo had a normal nutritional status. Factors influencing nutritional status included maternal characteristics (maternal height, education level, and family income) and child-related factors (frequency of food consumption). Conclusion: The study concluded that most toddlers affected by flooding in Sidomulyo have a normal nutritional status. Also, the determining factors of children’s nutritional status are maternal height, education level, family income and frequency of food consumption. The results of the study can be used as a reference for further research with the aim of maintaining children’s nutritional status in this area.